Mathematics Anxiety: What Have We Learned in 60 Years? - Dowker, Ann; Sarkar, Amar; Looi, Chung Yen (Frontiers in Psychology, 2016)
The construct of mathematics anxiety has been an important topic of study at least since the concept of 'number anxiety' was introduced by Dreger & Aiken (1957), and has received increasing attention in recent years. This paper focuses on what research has revealed about mathematics anxiety in the last 60 years, and what still remains to be learned. We discuss what mathematics anxiety is; how distinct it is from other forms of anxiety; and how it relates to attitudes to mathematics. We discuss the relationships between mathematics anxiety and mathematics performance. We describe ways in which mathematics anxiety is measured, both by questionnaires, and by physiological measures. We discuss some possible factors in mathematics anxiety, including genetics, gender, age and culture. Finally, we describe some research on treatment. We conclude with a brief discussion of what still needs to be learned.